Audit Delay Dilihat dari Aspek Audit Tenure, Financial Distress, Struktur Modal dan Ukuran Perusahaan - Ita Rakhmawati; Niawati Niawati (Universitas Islam Nahdlatul Ulama Jepara, 2023)
In order to achieve relevant information, financial statements presentation must be timely. It can help increase the public accountability. This study was conducted to obtain empirical evidence whether variables of audit tenure, financial distress, capital structure, and total asset influenced the delay in presentation of financial statements. The population of the study were all Indonesian Islamic Commercial Banks (BUS). By using purposive sampling technique with screening criteria, it was found 12 samples from 2017 to 2020 with 48 observations. This study used secondary data based on financial reports accessed through the IDX website and company pages. Through regression analysis, the results showed : (1) audit tenure did not have a significant effect on the delay of financial statements presentation, (2) financial distress derived through Debt to Asset Ratio (DAR) did not have a significant effect on the delay of financial statements presentation, (3) capital structure derived through Debt to equity ratio (DER) did not has a significant effect on the delay the delay of financial statements presentation, (4) Firm size derived through total assets does not have a significant effect on the delay of financial statements presentation.